IMAGE: INTEGRATE-Mediated Agrobacterium Genome Engineering - Aliu, Ephraim; Chen, Liang-Chun; Lee, Keunsub; Wang, Kan (Frontiers in Microbiology, 2025)
The ability to precisely engineer Agrobacterium strains is crucial for advancing their utility in plant biotechnology. We recently implemented the CRISPR RNA-guided transposase system, INTEGRATE, as an efficient tool for genetic modification in Agrobacterium. Despite its promise, the practical application of INTEGRATE in Agrobacterium strain engineering remains underexplored. Here, we present a standardized and optimized workflow that enables researchers to harness INTEGRATE for targeted genome modifications. By addressing common challenges, such as crRNA design, transformation efficiency, and vector eviction, this protocol expands the genetic toolkit available for Agrobacterium, facilitating both functional genomics and strain development for plant transformation. As a demonstration, we domesticated Agrobacterium rhizogenes K599 strain by deleting the 15-kb T-DNA region from its root-inducing plasmid pRi2659 and inactivating a thymidylate synthase gene to render the strain auxotrophic for thymidine. The protocol provides detailed guidance for each step, including target site selection, crRNA spacer cloning, Agrobacterium transformation, screening for targeted insertion and Cre/loxP-mediated deletion, and vector removal. This resource will empower new users to perform efficient and reproducible genome engineering in Agrobacterium using the INTEGRATE system, paving the way for broader adoption and innovation in plant biotechnology.